2019
DOI: 10.1016/j.jcot.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic and non-diabetic patients report equal symptom relief after arthroscopic capsular release of frozen shoulder

Abstract: Background: Frozen shoulder is a painful joint disease. Patients with diabetes seem to have worse clinical symptoms and surgery in this patient population is believed to be more common. The objective postoperative evaluation indicates inferior results when surgically treating diabetics, but no previous studies have investigated exclusively the subjective patient satisfaction with arthroscopic capsular release. Materials and methods: A total of 93 patients were included. All had persistent symptoms despite cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…There was no significant difference in preoperative Oxford shoulder score and postoperative Oxford shoulder score between the diabetic and the non-diabetic patients. Some studies also showed no significant difference in OSS between the diabetic and the nondiabetic patients (18,33,34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in preoperative Oxford shoulder score and postoperative Oxford shoulder score between the diabetic and the non-diabetic patients. Some studies also showed no significant difference in OSS between the diabetic and the nondiabetic patients (18,33,34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to previous studies ( Table 4 ) that compared the results of arthroscopic capsular release in diabetic and non-diabetic patients. Lyhne et al [ 19 ], although they performed anterior and posterior capsular release. They concluded that all patients, whether diabetic or non-diabetic, equally improved after arthroscopic capsular release when operated on regardless of diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…of patients Avg. age (years) Follow up Surgical technique Functional score Results Encountered complications Lyhne JM et al (2019) [ 19 ] 18 diabetic 75 non-diabetic Diabetic: 55.2 non-diabetic: 56 6 months Arthroscopic capsular release (360° arthroscopic capsulotomy). -Oxford Shoulder Score (OSS).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few well-designed studies of natural history of diabetic FS and comparison of clinical outcomes between diabetic FS and idiopathic FS after conservative treatments [ 14 , 24 ]. Also, the concept of resistance to treatment in diabetic FS has been mainly based on the results of studies about arthroscopic capsular release or manipulation under anesthesia [ 10 , 16 , 18 , 20 , 25 , 26 , 27 , 28 ]. Rill et al reported that patients with diabetes had a lower final Simple Shoulder Test score than patients without diabetes after non-operative treatments which were heterogeneous to each patient, but diabetes did not predict the need for surgery [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely-accepted by some experts that the treatment of diabetic patients with FS compared to that of idiopathic FS is more difficult and they show more resistance to treatment [15][16][17][18][19][20][21][22][23]. However, there have been few well-designed studies of natural history of diabetic FS and comparison of clinical outcomes between diabetic FS and idiopathic FS after conservative treatments [14,24].…”
Section: Discussionmentioning
confidence: 99%